Betesskador på lärkplantor - Frisk, Andreas (SLU/School for Forest Management, 2011)
The purpose of this study was to show how the Hybrid Larch (Larix eurolepis x) are used by large herbivores in terms of grazing and fraying. More specifically I studied how impact on the seedlings was affected by forest stand area, tree height and stem density (stems/ha).The survey was done in Jönköpings county in southern Sweden. About 50 % of all stems that are measured are damaged by grazing and 5,8 % was damaged from fraying. The conclusion of the study is that the biggest influencing factor is the height of the seedlings. The size of the stands and number off seedlings per hectare have almost no impact on the injuries on the seedlings. Fraying are common on trees smaller than 3 meters, and doesn’t occur on trees above that height. That can depend on the size of the branches on the lower part of the tree. In comparison with grazing damages on pine, in the ÄBIN survey, Larch has almost 10 times more damages. Keywords: Larch, Roe deer, Moose, Grazing, Forest damage, Fraying